Campus Canopy, 1937-01-22 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1937)
Cornelia Otis Skinner is Here -- Cradle Song Announced As Club Production -- Athletic Pledges Face Trying Week of Initiation -- Vocational Groups Report Study of Library Science -- Plans Are Announced By Athletic Council -- Spanish Paintings Are Displayed -- Feature Section Battle Ends -- McLain Says Sports, Literature Are Wise Leisure Pursuits
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals